Recent advances in the development of electrochemical hydrogen peroxide carbon nanotube–based (bio)sensors - Eguílaz Rubio, Marcos (2019)
The relevance of H2O2 as biomarker for different neurodegenerative diseases and cancer has been one of the most significant incentives for the development of new (bio)sensors that allow a more sensitive, selective, fast, and stable quantification of H2O2. In this regard, the association of carbon nanotubes with hemoproteins, nanoparticles, and other nanostructures and different electrochemical transducers has offered new avenues for the construction of innovative H2O2 bioanalytical platforms. This short review highlights the most relevant contributions in the field of electrochemical (bio)sensors for H2O2 based on carbon nanotubes published in the period 2016–2018.